Rural Development Programme (RDP): phase III report (1993-1995) - BRAC (© BRAC, 2016)
1.Rural savings & credit 2. Employment & income generation programme 3. Social development programme 4. Support services 5. Special programmes 6. Gender and environment 7. RDP programme management 8. Financial information